Perpustakaan Keliling Sebagai Upaya Meningkatkan Literasi dan Kesadaran Membaca Bagi Siswa - Cahaya Zakia A'yunin Juwita Hanum; Lita Argya Asta Dewi; Yayuk Widyastuti Herawati (Makkareso: Riset Pengabdian Masyarakat, 2024)
The mobile library is seen as an innovative solution that offers a dynamic and entertaining approach to promoting literacy. The research highlights the role of storytelling sessions and active student participation in enhancing the effectiveness of the mobile library. Teacher and school support are also considered crucial to the success of the program. Overall, the research supports the mobile library as an effective means of improving literacy and reading awareness among students, ultimately contributing to a more positive school community. The research method used is a qualitative research method with a descriptive approach. The results of the research show that the mobile library can stimulate students' reading interest and have a positive impact on their understanding of literature. Factors that affect the effectiveness of the mobile library include the presence of storytelling sessions, active student participation, and teacher and school support. The research aims to understand the impact of the mobile library on reading interest and the factors that affect its effectiveness at SDN 01 Kesamben. Keywords: Mobile library, Reading awareness, Students